Pelatihan Dan Demonstrasi Pembuatan Wayang Kain Flanel Sebagai Media Edukasi Seks Anak Usia Dini - Luluk, Hadiqotul; Widuroyekti, Barokah; Widyani, Inneke Putri; Purbosari, Nita Ryan; Syafi'i, Imam (Dedication : Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to enhance the capacity of early childhood education (ECE) teachers and parents in delivering appropriate sex education and toilet training through the use of flannel puppet media. The partners’ primary challenges were limited understanding and the lack of suitable instructional media for young children. The program was conducted over three days at PAUD Puspa Melati, Kaliwates, Jember, involving 20 participants from ten ECE institutions. The implementation methods included participatory training and demonstrations on the creation and utilization of the media. The results indicated an improvement in participants’ understanding and skills in teaching body awareness and personal hygiene concepts in an engaging manner. The program produced 20 sets of educational flannel puppets ready for classroom use. Overall, the initiative proved effective in strengthening collaboration between teachers and parents in fostering early childhood character development.